2022
DOI: 10.1097/md.0000000000028729
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sacubitril valsartan in treating heart failure with midrange ejection fraction after acute myocardial infarction in diabetic patients

Abstract: Objective to evaluate the clinical efficacy and safety of sacubitril valsartan in the treatment of heart failure (HF) with midrange ejection fraction after acute myocardial infarction (AMI) in diabetic patients. From January 2015 to July 2020, HF patients with diabetes mellitus complicated with AMI were retrospectively analyzed. According to the medication, they were divided into 2 groups, that is, sacubitril valsartan group (84 cases) and valsartan group (86 cases). Valsartan group took valsartan capsule (80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…The search identified 790 articles and 2 studies registered at Clinicaltrials.gov that met the inclusion criteria. After removing duplicates and screening, 9 studies ( 24 – 32 ) involving 1,369 participants were ultimately eligible for analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The search identified 790 articles and 2 studies registered at Clinicaltrials.gov that met the inclusion criteria. After removing duplicates and screening, 9 studies ( 24 – 32 ) involving 1,369 participants were ultimately eligible for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 9 studies, 6 were RCTs and 3 were non-RCTs. Based on our defined outcomes, 8 studies reported on CRR outcomes ( 24 , 25 , 27 32 ); 4 studies reported on biomarkers outcomes ( 25 , 29 – 31 ); 7 studies reported on MACE and HF outcomes ( 25 – 31 ); 6 studies reported on readmission outcomes ( 25 , 26 , 28 , 30 – 32 ); 4 studies reported on cardiac death outcomes ( 26 – 28 , 31 ); 4 studies reported on MI outcomes ( 26 – 29 ); while 3 studies reported on adverse side effects ( 25 , 28 , 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations